Pragmatic evaluation of a coproduced physical activity referral scheme: a UK quasi-experimental study. Issue 10 (1st October 2020) - Buckley, Benjamin JR; Thijssen, Dick HJ; Murphy, Rebecca C; Graves, Lee EF; Cochrane, Madeleine; Gillison, Fiona; Crone, Diane; Wilson, Philip M; Whyte, Greg; Watson, Paula M
Abstract : Objectives: UK exercise referral schemes (ERSs) have been criticised for focusing too much on exercise prescription and not enough on sustainable physical activity (PA) behaviour change. Previously, a theoretically grounded intervention (coproduced PA referral scheme, Co-PARS) was coproduced to support long-term PA behaviour change in individuals with health conditions. The purpose of this study was to investigate the effectiveness of Co-PARS compared with a usual care ERS and no treatment for increasing cardiorespiratory fitness. Design: A three-arm quasi-experimental trial. Setting: Two leisure centres providing (1) Co-PARS, (2) usual exercise referral care and one no-treatment control. Participants: 68 adults with lifestyle-related health conditions (eg, cardiovascular, diabetes, depression) were recruited to co-PARS, usual care or no treatment. Intervention: 16-weeks of PA behaviour change support delivered at 4, 8, 12 and 18 weeks, in addition to the usual care 12-week leisure centre access. Outcome measures: Cardiorespiratory fitness, vascular health, PA and mental well-being were measured at baseline, 12 weeks and 6 months (PA and mental well-being only). Fitness centre engagement (co-PARS and usual care) and behaviour change consultation attendance (co-PARS) were assessed. Following an intention-to-treat approach, repeated-measures linear mixed models were used to explore intervention effects. Results: Significant improvements in cardiorespiratory fitness ( p =0.002) and vascular health ( p =0.002) were found in co-PARS compared with usual care and no-treatment at 12 weeks. No significant changes in PA or well-being at 12 weeks or 6 months were noted. Intervention engagement was higher in co-PARS than usual care, though this was not statistically significant. Conclusion: A coproduced PA behaviour change intervention led to promising improvements in cardiorespiratory and vascular health at 12 weeks, despite no effect for PA levels at 12 weeks or 6 months. Trial registration number: NCT03490747 .